The effects of dietary changes on bone markers in postmenopausal vertebral osteopenia - İSLAMOĞLU, AYŞE HÜMEYRA; GÜNEŞ, FATMA ESRA (CHURCHILL LIVINGSTONE, 2020)
Background & aims: Nutrition is one of the most important environmental factors affecting the formation of osteopenia. The purpose of this study was to investigate the effects of dietary changes on bone formation and bone resorption markers of postmenopausal women with vertebral osteopenia. Methods: In this study, 108 women with postmenopausal vertebral osteopenia were included. Patients were observed for a month to identify their regular nutritional status. Before intervention, blood and urine samples were taken from all patients. Then, 2-day food consumption records were taken and the patients were divided into 4 groups. Different types of diets (opposite of their regular diets) were prepared for these groups (1: control, 2: reduced-carbohydrate, 3: reduced-protein, 4: reduced-sodium) and followed for 3 months. At the end of follow-ups, blood and urine samples were taken again and changes in osteocalcin (OC) and N-terminal telopeptide (NTX) levels were examined. Results: According to biochemical analysis, there was a significant decrease (p < 0,001) in OC levels in reduced protein group and an increase (p > 0,05) in reduced carbohydrate group. When NTX levels were assessed, a significant decrease (p < 0.001) in the reduced carbohydrate group and a significant increase in the reduced protein group (p < 0.05) were found. Conclusion: Our findings show that reduced carbohydrate diet protected whereas, reduced protein diet negatively affected bone health. Osteopenic individuals were thought to be able to improve bone health and their quality of life by early dietary intervention. (C) 2020 Elsevier Ltd and European Society for Clinical Nutrition and Metabolism. All rights reserved.
Keywords: Nutrition; Osteopenia; Protein; Carbohydrate; Sodium; LOW-FAT DIET; CALCIUM-METABOLISM; LOW-CARBOHYDRATE; PROTEIN-INTAKE; ELDERLY MEN; WEIGHT-LOSS; OSTEOPOROSIS; HEALTH; PREVENTION; SODIUM